A comparison of the effects of capital and labour taxes in CEE countries - Piotr Krajewski; Katarzyna Piłat (Comparative Economic Research. Central and Eastern Europe, 2022)
The aim of the article is to quantify and compare the impact of capital and labour tax on the economies of Central and Eastern Europe (CEE). The impulse-response functions presented in the paper show that output reacts differently to changes in the taxation of labour and capital. Although there is some heterogeneity in the magnitude and persistence of tax effects between the analysed CEE countries, the simulations generally indicate that the negative impact of increased capital taxation on GDP is stronger than for labour taxation. More importantly, however, the negative effects of higher taxation on capital are more persistent than in the taxation of labour. This is largely because higher capital taxation strongly reduces savings and the desired stock of capital, which has important long-term macroeconomic consequences.
Keywords: E62; H20; H30; 330; capital tax; labour tax; CEE countries